The relationship of breastfeeding patterns with the frequency of illness events in babies at the Siti Kholijah clinic in 2023 - Debora Paninsari; Nababan, Bunga Hariani; Azira Hazni; Azmarani, Azmarani (Jurnal EduHealth, 2024)
Mothers who do not exclusively breastfeed their children will have a negative impact on public health, causing upper respiratory tract infections (ARI), diarrhea, the baby's immune system, affecting the level of intelligence of the brain after adulthood and can trigger allergies, obesity and disease. intestines in premature babies and can also put the mother at risk of breast cancer. The aim of this research is to identify anything related to the relationship between breastfeeding patterns and the frequency of illness in babies at the Siti Kholijah Clinic in 2023. This type of research is an analytical study using a cross sectional design and Chi Square testing. The population in this study was all mothers who brought their babies for treatment at the Siti Kolijah Clinic in 2023 totaling 150 people and the method for collecting samples was Accidental Sampling. The results showed that 2 (8%) respondents had a predominant breastfeeding pattern with never getting sick. The incidence of illness was rare in 6 people (24%) with a predominant breastfeeding pattern. According to the Chi Square test, the score P (value) (0.002) < 0.05 is obtained, which means that there is a relationship between breastfeeding patterns and the frequency of cases of illness in babies at the Siti Kholijah Clinic in 2023. Suggestions for midwives to be able to provide information and counseling as well as education about breastfeeding patterns and events illness to all mothers who breastfeed and assist mothers directly by practicing correct breastfeeding methods for mothers in order to prevent the occurrence of illness in babies.